Pelatihan Pembuatan Video Reel Instagram Menggunakan Canva Pada Yayasan Widya Kapuas Kalbar - Eri Bayu Pratama; Wahyutama Fitri Hidayat; Hermanto Hermanto; Muhamad Syarif; Ade Hendini (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2022)
The development of information and communication technology today has changed the way humans interact with each other. Social media is one of the media that allows humans to interact without being limited by space and time. The positive impact of using social media can be used as a medium of information. However, this positive impact must be accompanied by an increase in digital literacy, especially in designing information that will be conveyed to the public, one of which is through the Instagram application rails. This service has the main goal of providing training in the form of making Instagram reels using the Canva application. The target of community service activity partners is in the form of non-formal institutions, the Yayasan YAWIKA Kota Pontianak. The method of implementation is done offline by coming directly at the location of community service. The results of this activity showed satisfactory results from the participants as well as increasing digital literacy, especially in optimizing social media as a medium of information and using the Canva application.